Essential Oils from Papaver rhoeas and Their Metabolomic Profiling - Valeria Cavalloro; Francesco Saverio Robustelli della Cuna; Alberto Malovini; Carla Villa; Cristina Sottani; Matteo Balestra; Francesco Bracco; Emanuela Martino; Simona Collina (Metabolites)
Background/Objectives: Essential oils (EOs) have been exploited by humans for centuries, but many sources remain poorly investigated, mainly due to the low yields associated with conventional extraction. Recently, new techniques have been developed, like solvent-free microwave extraction (SFME), able to enhance efficiency and sustainability. The use of Papaver rhoeas L. in traditional medicine has led researchers to investigate non-volatile fractions, but there are little data available on EOs. Methods: In the present work, we prepared EOs from the petals and leaves of P. rhoeas by SFME. GC/MS analysis of EOs revealed the presence of 106 compounds belonging to 13 different classes. Isomers of the different alkenes were identified thanks to an alkylthiolation reaction. Results: The results highlighted a predominance of saturated and unsaturated hydrocarbons, alcohols, and esters that might suggest a specific relationship with pollinators. Each population has been compared using PCA, heatmap, and barplot tools, highlighting differences in terms of composition by both comparing leaves and flowers and hill and lowland samples. Furthermore, cantharidin, a metabolite usually produced by insects, was detected in the flowers, possible present for attractiveness purposes. Conclusions: These results could contribute to ensuring a better understanding of the pollination process and of the biological activities of EOs from P. rhoeas.